IMPORTANT FACTORS FOR THE USE OF IMAGINATION IN SCHOOL NATIVE LANGUAGE LESSONS - Sh. Yusupova; Nigorakhon Mamajonova (American Journals, 2023)
This article will talk about the use of textbooks in school education, its important factors. A reflection will be made on the useful and necessary aspects of the new textbook. There is talk about the influence of imagination on the mother tongue lessons and on the mother tongue, its beneficial factors.The introduction of the 7th grade to topics in the textbook of the native language.
Keywords: Third Renaissance, unconventional education, intellect, imagination, fantasy, vitamin C, contemplation, PISA, methodology